Comparing pathological complete response rate using oral capecitabine versus infusional 5‐fluorouracil with preoperative radiotherapy in rectal cancer treatment. Issue 1 (5th October 2017) - Jootun, Narotam; Evans, Tess; Mak, Jackie; Makin, Greg; Platell, Cameron
Abstract : Background: Infusional 5‐fluorouracil (5‐FU) has been the standard radiation sensitizer in patients undergoing preoperative long‐course chemoradiotherapy (CRT) for locally advanced rectal cancer in Australia. Capecitabine (Xeloda) is an oral 5‐FU prodrug of comparable pharmacodynamic activity, currently preferred in place of 5‐FU infusion, its established counterpart in neoadjuvant CRT for rectal cancer. The few studies quantifying pathological complete response (pCR) of Xeloda versus 5‐FU have produced inconsistent results. We reviewed our own data to determine if the rates of pCR of oral capecitabine were non‐inferior to intravenous 5‐FU in patients undergoing neoadjuvant CRT for rectal cancer. Methods: A retrospective study was performed from a prospectively kept database. Four hundred and fifty‐two patients received preoperative CRT from January 2006 to January 2016. Pelvic radiotherapy was delivered concurrently with capecitabine ( n = 42) or infusional 5‐FU ( n = 341). The remaining received different chemotherapy regimens. Surgery was performed 6–12 weeks of CRT completion. Pathological responses were assessed using Dworak regression grading score (0–4). Clinical outcomes were evaluated in terms of local control and recurrence‐free survival. Results: The proportion of patients who had a tumour regression score of 4 (pCR) after CRT was 4/42 (9.5%) in the capecitabine group and 71/341 (20%) in the infusional 5‐FU group ( P = 0.082). pCR was an independent predictor for survival in this group of patients (hazard ratio: 0.002, P = 0.0001, 95% confidence interval: 0.0001–0.027). Conclusion: The use of capecitabine as neoadjuvant chemotherapy in patients with rectal cancer was associated with a reduced rate of pCR. However this difference did not achieve statistical significance.